A rare case of Autosomal Dominant Hyper IgE syndrome - Menon, Aakash S.; Jayasimhan, Karthika; Shekhar Reddy, Ganta Chandra; Garud, Balakrushna; Suresha, Suresha (Journal of Neonatal Surgery, 2025)
Inborn Errors of Immunity (IEI), once called Primary Immunodeficiency Disorders, are rare genetic conditions that weaken the immune system, making individuals prone to frequent infections, allergies, or even autoimmune problems. These conditions usually show up in childhood and vary widely in how they affect people. One such condition is Hyper IgE Syndrome (HIES), a rare disorder known for high levels of IgE antibodies, recurring skin and lung infections, and eczema-like rashes. It can also involve bone, dental, and connective tissue abnormalities. There are two main types: the autosomal dominant form (AD-HIES), caused by mutations in the STAT3 gene, and the more severe autosomal recessive form (AR-HIES), often involving other genes like DOCK8. We present a case of a 7-year-old girl with the dominant form of HIES, who had a long history of skin infections, dry skin and recurrent otitis. Genetic testing confirmed a mutation in the STAT3 gene. With supportive care and preventive treatment, her condition improved significantly. This case highlights how important it is to recognize signs of IEI early. Thanks to modern genetic testing, many of these disorders can now be identified sooner, leading to better outcomes through targeted treatments and ongoing care